The Graveyard Book - Gaiman, Neil, 1960-; McKean, Dave, 1963- (New York : HarperCollins, 2010)
After the grisly murder of his entire family, a toddler wanders into a graveyard where the ghosts and other supernatural residents agree to raise him as one of their own.
GRL: X
Ages 10 up.
Newbery Medal, 2009
Hugo Award, 2009
Locus Award, 2009
Carnegie Medal, 2010
Keywords: Dead -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction; Orphans -- Fiction; FICTION / Horror